Compliance with antiretroviral treatment among patients with AIDS - a descriptive study - Léa LMMB Barroso; Karla KCP Pereira; Paulo PCA Almeida; Marli MTGG Galvão (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
Objective: To assess compliance with antiretroviral therapy (ARVT) among HIV/aids patients and to propose strategies that would facilitate it. Methods: A study of the descriptive and exploratory type was conducted at a specialized outpatient clinic in Fortaleza-CE between May and June 2004, with Thirty-eight patients with aids taking ARVT of a structured interview. Compliance was calculated on the basis of the sum of the total quantities of ARVT pills taken during the three days preceding the interview. A patient who used at least 95% of the amount of ARVT prescribed was considered to be compliant. Results: There was a predominance of males aged 30 years or more, with elementary schooling, married, Catholic, unemployed and with a family income of up to one minimum wage. The rate of compliance was 71%. Correlation of the different variables showed that non-compliance was related to male sex, age range between 20 and 29 years, low educational level, being single, being unemployed, and having low financial resources. Conclusions: Among the different socioeconomic variables, age showed statistical significance, i.e., the older individuals tended to show more compliance. It is assumed that the intervention of health professionals directly aimed at improving the use of specific medications may act as a facilitating factor in the process and maintenance of the expected pattern of compliance. In this respect, we suggest that adequate organization of the service and of a multi-professional team, the creation of ties and the formation of adhesion groups, in addition to individual care, may respond to the expectations and the doubts due to the continuous use of ARVT.